Pengolahan falsafah yin yang dalam kitaran pembentukan manusia melalui video eksperimental - Goh, Hui Ling. (Universiti Malaysia Sarawak (UNIMAS), 2010)
This artwork seeks to symbolically represent a small but significant part of the intricacies in the decisions and paths we choose in life. In Chinese philosophy, the Yin Yang symbol represents opposing forces or aspects. Like a strand of DNA, so simple; and yet is capable of creating the most complex creatures on Earth…… You and Me!